Anti-mutagenic Activity of Oxycarotenoid-rich Extracts Isolated from Coriandrum Sativum and Murraya koenigii - Anish, Anusha; Abdulkadir, Sherena Padinjarevattom; Theru, Annamala Panthapulakkil; Kurian, Mukkadan Joseph (Asian Pacific Journal of Cancer Biology, 2020)
Introduction: Edible and medicinal plants contain active principles that can act as antimutagens, and hence their intake may be useful for human cancer prevention. Green leafy vegetables are important sources of carotenoids which possess antioxidant, anti-inflammatory and antimutagenic properties. Objective: To study the antimutagenic activity of oxycarotenoid-rich extracts isolated from Coriandrum sativum (coriander leaves) and Murraya koenigii (curry leaves). Methods: Oxycarotenoid-rich extracts isolated from Coriandrum sativum (coriander leaves) and Murraya koenigii (curry leaves) were investigated for antimutagenic activity in vitro by Ames test using Salmonella typhimurium strains TA 98 and TA 1535. Mutagens used were, nitro-o- phenylenediamine (NPD) (20μg/plate) and N-methyl- N-nitro-N-nitrosoguanidine (MNNG) (1μg/ plate). Results: The results revealed that oxycarotenoid-rich extracts isolated from Coriandrum sativum (coriander leaves) and Murraya koenigii (curry leaves) administered at doses of 1.0 mg, 2.5 mg and 5 mg per plate significantly inhibited mutagenicity induced by NPD and MNNG. Conclusion: These findings suggest that oxycarotenoid- rich extracts isolated from Coriandrum sativum (coriander leaves) and Murraya koenigii (curry leaves) have antimutagenic properties.